Modelado del espacio-tiempo en el interior de una estrella de neutrones en rotación con un cuadrupolo agregado de forma perturbativa - Morales Montenegro, Julio César (2021)
The potentials and multipolar parameters for a neutron star internal space-time model are calculated in a perturbative series using the angular velocity as perturbation parameter. Twelve equations of state are considered, five of them are artificial based on a selected equation of state up to nuclear saturation density that are continued with five pure polytropes in order to study rigidity effects in our model, and the remaining seven equations are based on nuclear models. The mass and radius curves are calculated, and then the perturbations due to rotation are added. The ellipticity, the moment of inertia and the mass quadrupole are also calculated. It is found that the normalized mass quadrupole, Qn=Q/MR^2e^2, with "e" as the ellipticity, is near the classical value Q/Me^2R^2 = 0,2964 - 0,0652 M/M_O ~ 0.2, when we compare with equations of state based on nuclear models, it yields a maximum error of 6%. This formula could be used to estimate parameters in ray-tracing applications (like the equatorial and polar radius ratio) and in gravitational waves models along the I-Love-Q relations. The perturbation potentials are much less than unity even for the highest measured frequency (f=716 Hz) which validates our approximation.